Sleep patterns in adults and children with less common forms of diabetes - Arosemena, Marilyn; Salguero, Maria V.; Greeley, Siri Atma W.; Naylor, Rochelle N.; Tasali, Esra; Philipson, Louis H. (Frontiers in Endocrinology, 2025)
ObjectiveTo review the current evidence on sleep patterns in relation to glucose control in adults and children with type 1 diabetes (T1DM) and monogenic diabetes.MethodsWe searched for the literature pertaining to T1DM and monogenic diabetes with reported sleep patterns, along with glycemic control, in PubMed. This review aimed to examine the current evidence on the relationship between sleep patterns and diabetes management and possible mediating mechanisms for this relationship in adults and children with T1DM and monogenic diabetes. We reviewed articles published from inception until 2023.ResultsTwenty-five clinical studies met the eligibility criteria and were included. Children with T1DM with higher sleep variability had higher glucose levels, and those with higher glucose variability had more sleep disruptions. Comparing children with suboptimal [hemoglobin A1c (HbA1c) ≥ 7.5%] and optimal glucose control, those with suboptimal control had shorter sleep duration. There was no higher prevalence of obstructive sleep apnea (OSA) in children with T1DM compared to controls, but in T1DM, those who had OSA had higher glucose levels. Adults with T1DM had a high prevalence of poor sleep quality and were also sleeping less than the recommended hours for their age. Poor sleep quality and short sleep duration correlated with higher glycemic variability. First-generation automated insulin delivery systems did not improve sleep patterns in T1DM, but other strategies, including coaching and counseling, proved to be effective. Monogenic diabetes data also suggest poor sleep quality, short sleep duration, and high rates of sleep apnea.ConclusionT1DM subjects seem to have worse sleep patterns, especially those with suboptimal glucose control. Monogenic diabetes data are limited, but they also suggest poor sleep patterns. Rigorous interventional studies are needed to further elucidate the sleep–diabetes relationship. Future research could provide insights into strategies that could effectively improve sleep in people living with diabetes.